2004
DOI: 10.1177/1073858403259950
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Activation and Neuroinflammation in Chronic Pain and Opioid Tolerance/Hyperalgesia

Abstract: One area that has emerged as a promising therapeutic target for the treatment and prevention of chronic pain and opioid tolerance/hyperalgesia is the modulation of the central nervous system (CNS) immunological response that ensues following injury or opioid administration. Broadly defined, central neuroimmune activation involves the activation of cells that interface with the peripheral nervous system and blood. Activation of these cells, as well as parenchymal microglia and astrocytes by injury, opioids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
275
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(288 citation statements)
references
References 57 publications
10
275
2
1
Order By: Relevance
“…Iba-1 or MHC class II expression. The observed differential immunoreactivity in GFAP between WT and CD4 KO mice is consistent with the concept that astrocytes have been associated with the maintenance of L5Tx-induced neuropathic pain [3]. Our previous observations of increases in the costimulatory molecule B7.2 and MHC class II in the lumbar spinal cord post L5Tx and significantly decreased pain behaviors post L5Tx in MHC class II KO mice [4,6,7] support the involvement of T lymphocyte-mediated adaptive immunity in pain.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Iba-1 or MHC class II expression. The observed differential immunoreactivity in GFAP between WT and CD4 KO mice is consistent with the concept that astrocytes have been associated with the maintenance of L5Tx-induced neuropathic pain [3]. Our previous observations of increases in the costimulatory molecule B7.2 and MHC class II in the lumbar spinal cord post L5Tx and significantly decreased pain behaviors post L5Tx in MHC class II KO mice [4,6,7] support the involvement of T lymphocyte-mediated adaptive immunity in pain.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that glial activation post L5Tx plays a key role in L5Tx-induced behavioral hypersensitivity [3]. Therefore, we examined astrocytic and microglial responses at day 7 post L5Tx in both WT and CD4 KO mice via immunohistochemistry.…”
Section: Lumbar Spinal Cord Glial Responses Post L5txmentioning
confidence: 99%
See 1 more Smart Citation
“…Because inhibition of JNK suppresses SNL-induced phosphorylation of c-Jun in spinal astrocytes (Zhuang et al, 2006a), JNK activation is likely to regulate gene transcription in spinal astrocytes via activation of the transcription factor c-Jun and other transcription factors such as ATF-2. After nerve injury, there is increased synthesis in the spinal cord of inflammatory mediators such as cytokines , nitric oxide (NO), which is produced by inducible NO synthase (iNOS), and prostaglandin E2 (PGE2) (produced by either COX-1 or COX-2); all these mediators and enzymes are implicated in pain sensitization (Samad et al, 2001;Watkins et al, 2001;DeLeo et al, 2004;Ji and Strichartz, 2004). Mixed lineage kinases (MLK) are specific JNK kinases.…”
Section: Activation Of the Jnk Cascade In Spinal Astrocytes And Neuromentioning
confidence: 99%
“…CD11b, TLR4 and CD14) within several hours . Initially, microglia appear to be activated, which activates astrocytes (Aldskogius and Kozlova, 1998;DeLeo et al, 2004). Specifically, nerve injury upregulates several receptors, such as the chemokine receptor CX3CR1 and ATP receptor P2X4 in spinal microglia.…”
Section: Introductionmentioning
confidence: 99%